The “Sweet Spot” in the Middle: Why Do Mid-Scale Farms Adopt Diversification Practices at Higher Rates? - Esquivel, Kenzo Emiliano; Carlisle, Liz; Ke, Alison; Olimpi, Elissa M.; Baur, Patrick; Ory, Joanna; Waterhouse, Hannah; Iles, Alastair; Karp, Daniel S.; Kremen, Claire; Bowles, Timothy M. (Frontiers in Sustainable Food Systems, 2021)
In the past few decades, farmers and researchers have firmly established that biologically diversified farming systems improve ecosystem services both on and off the farm, producing economic benefits for farmers and ecological benefits for surrounding landscapes. However, adoption of these practices has been slow, requiring a more nuanced examination of both barriers and opportunities to improve adoption rates. While previous research has demonstrated that both individual and structural factors shape farmers' decisions about whether to adopt diversification practices, this study aims to understand the interaction of these individual and structural factors, and how they relate to farm scale. Based on 20 interviews with organic lettuce growers on the Central Coast of California, as well as 8 interviews with technical assistance providers who work with these growers, we constructed a typology to help elucidate the distinct contexts that shape growers' decisions about diversification practices. This typology, which reflects the structural influence of land rent and supply chains, divides growers into three categories: limited resource, mid-scale diversified, or wholesale. In this economic context, limited resource and wholesale growers both experience significant barriers that constrain the adoption of diversification practices, while some mid-scale diversified growers have found a “sweet spot” for managing agroecosystems that can succeed in both economic and ecological terms. The key enabling factors that allow these farmers to choose diversification, however, are not directly related to their farm size, but have more to do with secure land tenure, adequate access to capital and resources, and buyers who share their values and are willing to pay a premium. By focusing on these key enabling factors with targeted policies, we believe it is possible to encourage diversification practices on farms at a variety of scales within California's Central Coast.